Pengaruh Stress, Menarche Dini dan Perilaku Konsumsi Fast-Food Terhadap Dismenore Primer pada Remaja Putri di SMPN 01 Sukabumi - Hamidah, Ratih; Pertami, Jurina; Daulan, Lita Yazid (Media of Health Research, 2024)
Primary dysmenorrhea is menstrual pain that occurs without any abnormalities in the genital organs and almost always appears for the first time in women aged 20 years or younger after their ovulation cycle has stabilized. The prevalence of dysmenorrhea worldwide is substantial, with more than 50% of women in each country experiencing menstrual pain. This study is an analytical study using a quantitative approach with a cross-sectional design. Data were collected through a survey method using questionnaires that had been tested for validity and reliability, and analyzed using univariate and bivariate analysis. Among 187 adolescent respondents, 137 (73.3%) experienced dysmenorrhea. Of these, 110 (58.8%) had experienced early menarche, 115 (61.5%) experienced stress, while 72 (38.5%) did not. Additionally, 141 respondents (75.4%) reported regular fast-food consumption behavior. The Chi-Square statistical test showed that the majority of dysmenorrhea cases occurred among respondents with early menarche (p-value = 0.003; OR = 2.87), those who experienced stress (p-value = 0.014; OR = 2.40), and those with fast-food consumption behavior (p-value = 0.04; OR = 2.19). There is a significant relationship between early menarche, stress, and fast-food consumption behavior and the incidence of primary dysmenorrhea among female adolescents at SMPN 01 Sukabumi. Recommendation: Strategic steps should be taken to educate adolescents on healthy lifestyles, including meeting nutritional needs through a balanced diet as per the "Isi Piringku" guidelines, providing counseling to reduce potential stress, and raising awareness about the risks associated with fast-food consumption.